New method for the calculation of the temperature behaviour of the piezoelectric resonator parameters - J. ZELENKA (Archives of Acoustics)
The derivatives G^(1)_ijkl and G^(2)_ijkl of the elastic stiffnesses which described the elastic properties of thermally deformated and with small-amplitude vibrated quartz plates were defined by Lee and Yong in 1985. The values of the derivatives were computed and are given in the paper. The relations for computing the temperature coefficients of frequency suitable for the more precise expression of the temperature behaviour of quartz plates vibrated in thickness modes are published.